COVID-19 Worry and Mental Health Among the Economically Active Population in Guangdong, China - Yong, Xin; Zhang, Li (Frontiers in Public Health, 2022)
Background The rapid spread of the coronavirus disease 2019 (COVID-19) pandemic has caused people to worry, which has affected their mental health. This study aimed to access the impact of COVID-19 worry on the mental health of the economically active population (EAP) in a province of China. Methods An online cross-sectional survey study was conducted during an outbreak of COVID-19 in Guangdong, China. The survey used the 12-item General Health Questionnaire (GHQ-12) to evaluate participants' mental health status and was completed by 1,584 of the 1,708 participants (a response rate of 92.74%). Ordinary least squares (OLS) regression models were used to identify the correlation between COVID-19 worry and mental health. Results Approximately 42.05% of participants reported that they were very worried or extremely worried about the COVID-19 pandemic. COVID-19 worry was negatively correlated with mental health (p < 0.01) and exhibited a stronger influence on the mental health of participants who were male, younger (aged 16–45), or unemployed than on the mental health of participants who were women, older (aged over 45), or employed. Conclusion The findings suggest that COVID-19 worry has generated new inequalities in mental health among the EAP of China. The government should provide more public reassurance and psychological support to the EAP to mitigate the effects of COVID-19 worry and prevent mental health disorders.